Pemberdayaan Masyarakat Melalui Pembuatan Buket Bunga untuk Menunjang Eksistensi Desa Wisata Banabungi - Tri Astuti; Husnah Katjina; Wa Ode Adriani Hasan; Fandi Setiawan; Dita Safitri (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
The ecotourism concept was formulated by the government in the mid-1990s. The stretch of ecotourism began to be felt when tourism villages popped up everywhere. Banabungi Village, which is located in Pasarwajo District, has an icon of pride in Buton Regency, namely the asphalt mining company PT. WIKA BITUMEN and Banabungi port. Banabungi Village has many attractive locations, such as the Kali Lakua and Kali Sollo tourist parks, Rainbow Bridge, and the Dive Center. The community are mostly high school graduates and work as fishermen and traders. The natural conditions and environment are still very natural, with many ethnic plants typical of the coastal area, such as weeds and other shrubs. These plants have not been used economically and grow wild everywhere. The purpose of this community service activity is to utilize the potential of endemic plants so that they can have high economic value. The method used is to provide counseling about the importance of utilizing the natural potential around us to increase family income and provide training in making flower bouquets from dried and fresh plants. The community members were very enthusiastic and very interested in the training on how to dry wild plants and arrange them into beautiful flower bouquets that are marketable.